Tissue Nitrogen- and Phosphorus-Content of Gracilaria coronopifolia J. Agardh from Iligan Bay in Relation to the Seawater Nutrient Concentration - Rosales-Apao, Patricia; Schramm, Winfrid (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
Tissue nitrogen- and phosphorus-content of Gracilaria coronopifolia J. Agardh were analysed from samples collected in Iligan Bay (Initao, Misamis Oriental, Northern Mindanao, Philippines) over a 20-month period. The samples were oven-dried (24 h at 70 ° C) and gound to fine powder for nitrogen analysis employing a Carlo Erba C/H/N Elemental Analyser. Tissue phosphorus content was measured photometrically as phJsphate following digestion in a concentrated HCl of combusted materials (5 h at 550 ° C). Tissue nitrogen-and phosphorus-content (0.7 to 2.76 % g dw and 0.03 to·0.26% g dw, respectively) varied throughout the collecting period without showing distinct seasonal trends. The results may show that nutrient acquisition and primary productivity of seaweeds are not solely a function of the external nutrient concentration, but are influenced by time dependent processes such as nutrient accumulation and internal nutrient levels, adaptatjon and physiological state of the seaweeds.